2019
DOI: 10.1111/avj.12857
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chlamydiaceae in ocular swabs from Australian pre‐export feedlot sheep

Abstract: Infectious Ovine Keratoconjunctivitis (IOK) is a contagious ocular disease of sheep. A range of organisms have been observed as the aetiological agents of IOK. In this study, the presence of chlamydial pathogens (C. pecorum, C. abortus, C. psittaci) in conjunctival swabs was tested for. The swabs were collected from sheep with varying grades of IOK in an Australian pre‐export feedlot. The sheep had been rejected from a shipment because of the eye disease. The relative contribution of chlamydial pathogens to IO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…Prior to genotyping, the C. pecorum positive DNA samples from six liver and two cotyledon samples taken from eight aborted and/or stillborn lambs from four different farms (Additional file 2 ) were quantified for C. pecorum genome copy number (tested in duplicate) using standard curve calibrated and High Resolution Melt (HRM) C. pecorum qPCR assay [ 43 ]. The genome copy number/µL in samples ranged from 3.41 × 10 2 –2.47 × 10 5 copies/µL DNA template, with geometric mean of 7.26 × 10 3 copies/µL (Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Prior to genotyping, the C. pecorum positive DNA samples from six liver and two cotyledon samples taken from eight aborted and/or stillborn lambs from four different farms (Additional file 2 ) were quantified for C. pecorum genome copy number (tested in duplicate) using standard curve calibrated and High Resolution Melt (HRM) C. pecorum qPCR assay [ 43 ]. The genome copy number/µL in samples ranged from 3.41 × 10 2 –2.47 × 10 5 copies/µL DNA template, with geometric mean of 7.26 × 10 3 copies/µL (Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Each amplification assay was performed as recently described and calibrated using serially diluted known standards. A positive (cultured isolates C. pecorum E58, C. psittaci CR009 and C. abortus B577 DNA) and negative (MilliQ water) control was included in each run, with all samples tested in duplicate . Bovine mitochondrial DNA ( Cytochrome B) was used as an internal standard to assess the integrity of the sample and the presence and/or absence of PCR inhibitors .…”
Section: Chlamydia Detection Rates In Samples From Dairy Herds and Onmentioning
confidence: 99%
“…As such, the use of these assays may be contributing to unnecessary rejection of animals in various international markets that require Cab testing, consequently reducing profitability and incurring losses to the industry. A recent study screening for chlamydial pathogens in conjunctival swabs collected from rejected sheep with varying grades of infectious ovine keratoconjunctivitis (IOK) from an Australian pre-export feedlot also demonstrated that Cpec ocular infections are common in both sheep presenting with IOK, as well as healthy animals [89]. These findings further support a role for Cpec infections in economic losses to the Australian sheep industry.…”
Section: Cpec Infections In Livestock-a Contributor To Economic and Pmentioning
confidence: 81%
“…In contrast, until recently the reports in Australia were anecdotal, inconclusive and rare. Since the description of Cps infections in horses, Cps has been detected in a limited number of domesticated cattle and sheep [88,89], however wider surveys are warranted to truly elucidate whether the livestock animals are indeed commonly infected with this pathogen and represent "new" reservoirs, or if Cps detection is a result of "spill-over" from birds and/or environmental exposure ( Figure 1A).…”
Section: Chlamydia Psittaci-a Parrot Pathogen With Zoonotic Potentialmentioning
confidence: 99%
See 1 more Smart Citation